The Third Gate : Jeremy Logan #3 - Child, Lincoln (New York : Doubleday, 2012)
Believing he has discovered the burial chamber of a near-mythical Egyptian pharaoh and a mystical double crown, famed archaeologist Porter Stone and his team suffer bizarre accidents that Professor Jeremy Logan is brought in to investigate.
Keywords: College teachers -- Fiction; Americans -- Middle East -- Fiction; Colleges and universities -- Faculty -- Fiction; Americans -- Middle East -- Fiction; Suspense fiction; Mystery fiction